The role of institutions and firm heterogeneity for labour market adjustment: cross-country firm-level evidence - Gal, Peter N.; Hijzen, Alexander; Wolf, Zoltan (Bonn, 2013)
"This paper investigates the role of policies and institutions for aggregate labour market dynamics during the recent financial crisis using firm-level data. First, it provides comparable estimates on firm-level labor adjustment by country, industry and firm size. Second, using variance decomposition methods, it shows that differences in firm-level labor adjustment accounts for about 40% of the cross-country variation in aggregate employment growth at the outset of the crisis. We interpret this as evidence that differences in institutional settings accounted for a substantial part of the variation in aggregate employment growth. Third, we find that stronger protection for regular workers is associated with lower (higher) employment (earnings-per-worker) response in the wake of output shocks. This suggests employment protection shifts the burden of adjustment from the extensive to the intensive margin. However, in explaining the diverse cross-country patterns in employment adjustment during the crisis, the impact of employment protection alone seems to be small."